A STUDY ON THE CURRENT PRESCRIBING PATTERNS OF DIPEPTIDYL PEPTIDASE 4 INHIBITORS IN A MULTI SPECIALITY HOSPITAL OUTPATIENT SETTING - MUSHTAQ, SUMAYYA; MAYEE, K. RAWHEENA; AMREEN, SANA; SATYANARAYANA, V.; YERRAMILLI, APARNA; RAMAKRISHNAN, SANTOSH (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate the current prescribing pattern of dipeptidyl peptidase 4 inhibitors in a multi specialty hospital outpatient setting. Method: The study was a retrospective descriptive analysis of consecutive patients with DPP4 inhibitors prescribed and attending the diabetic clinic of the tertiary care hospital. Patient data was collected in relation to drugs prescribed, lab parameters, co morbid conditions and diabetic complications. The prescribing patterns of DPP4 inhibitors was studied and evaluated. Results: During the study, prescription of 74 patients who were initiated with dipeptidyl peptidase 4 inhibitors was reviewed. Sitagliptin (51%) was the most prescribed drug. The most commonly prescribed combinations were Metformin and DPP4 inhibitor (62%) as 2nd line agent, Metformin + Sulphonylureas + DPP4 inhibitor (44%) as 3rd line agents. In our study DPP4 inhibitors were initiated in patients with higher body mass index (BMI) and Glycated hemoglobin (HbA1c) greater than 9%. Conclusion: Our evaluation revealed the most commonly prescribed DPP4 inhibitor to be Sitagliptin. Initiation of DPP4 inhibitor was more commonly seen as a 3rd line agent. As DPP4 inhibitors are recently approved drugs educational intervention regarding their appropriate use is required. Key words: Diabetes mellitus, Dipeptidyl peptidase 4 inhibitors, Sitagliptin, prescribing patterns, Hyperglycemia.